Mothering Sunday : a romance - Swift, Graham, 1949- (Alfred A. Knopf, 2016)
"From the Booker Award winner: a luminous, profoundly moving work of fiction that begins with an afternoon tryst in 1924 between a servant girl and the young man of the neighboring house, but then opens to reveal the whole life of a remarkable woman. Twenty-two-year-old Jane Fairchild, orphaned at birth, has worked as a maid at one English country estate since she was sixteen. And for almost all of those years she has been the secret lover to Paul Sheringham, the scion of the estate next door. On an unseasonably warm March afternoon, Jane and Paul will make love for the last time--though not, as Jane believes, because Paul is about to be married--and the events of the day will alter Jane's life forever. As the narrative moves back and forth from 1924 to the end of the century, what we know and understand about Jane--about the way she loves, thinks, feels, sees, remembers--deepens with every beautifully wrought moment. Her story is one of profound self-discovery and through her, Graham Swift has created an emotionally soaring and deeply affecting work of fiction"--